Diagnostic value of fractional exhaled nitric oxide in differentiating the asthma-COPD overlap from COPD: a systematic review and meta-analysis. Issue 6 (3rd June 2022) - Zhang, Chuchu; Zhang, Meng; Wang, Yalei; Su, Xiaojie; Lei, Ting; Yu, Haichuan; Liu, Jian
ABSTRACT: Background: Patients with asthma-COPD overlap (ACO) account for 15–20% of chronic obstructive pulmonary disease (COPD), and the incidence increases with age. Patients with ACO have worse outcomes without proper treatment than those with COPD alone. However, the current diagnostic criteria of ACO are mainly based on symptom features and lack of objective indicators. Recently, several studies have demonstrated that fractional exhaled nitric oxide (FeNO) was higher in ACO than in COPD alone. Thus, this study aims to determine the diagnostic value of FeNO in differentiating ACO from COPD and assisting clinical decision-making. Methods: We conducted searches in the databases including PubMed, Web of Science, Cochrane Library, and Embase to extract original studies. Results: In all, 10 studies involving 1335 participants were included in this meta-analysis. FeNO level was significantly higher in ACO patients than in patients with COPD alone (WMD = 11.15ppb, 95%CI = 9.01‒13.28; I 2   = 18.0%, p = 0.000). The sensitivity and specificity of FeNO in distinguishing ACO from COPD were both 0.71, and the area under the receiver-operating characteristic curve (AUC) was 0.76, indicating that FeNO has moderate diagnostic accuracy in differentiating ACO from COPD. Conclusion: FeNO as an inflammatory biomarker is effective in differentiating ACO from COPD and assisting in clinical decision-making.